Konsep Fahishah dalam Al Qur'an; Studi Kajian Tematik Dalam Perspektif Tafsir̄ - Fitriawan, Aidul (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
Qur'an states that in the creation of human beings, they had two tendencies, namely the tendency to do good and to do evil. In explaining these two matters, the Qur'an uses several terms. For example, in terms of goodness, the Qur'an uses several terms, such as khair, ma'ruf, hasanah, and others. Vice versa, the Qur'an also uses several terms for crimes, for example, sû', sayyiât, fahsyâ, fâhisyah, and others. This study emphasizes the use of the word fahisyah in interpreting evil or ugliness. This research is library research. In collecting data, the use that was applied was a literature search with the maudhū'i method approach or commonly known as thematic studies. This research aims to find the concept and meaning of the word fahisyah and its contextualization in the present as well as some efforts to prevent it. The results of this study indicate that (1) fāh̠isyah is a heinous act that exceeds the limits of reasonableness and acts that are strictly prohibited by the Shari'a such as all acts of sexual deviation. (2) Some experts also explain that fāh̠isyah is a heinous act such as shirk, homosexuality, adultery, marrying one's father's wife, as well as perpetrators of LGBT.